Pengaruh Penggunaan Pupuk Kimia Terhadap Pendapatan Usahatani di Desa Duriaasi Kecamatan Wonggeduku Kabupaten Konawe - Echi Hastiawati; La Karimuna; Sarty Syarbiah (STIKes Ibnu Sina Ajibarang, 2025)
The purpose of this research is to analyze the income of cucumber farming and analyze the effect of the use of chemical fertilizers on cucumber farming income in Duriasi Village, Wonggeduku District, Konawe Regency. Sample determination was carried out by census. Where in Duriaasi Village there are 21 cucumber farmers. The analysis uses the income analysis formula and multiple non-linear regression with the equation transformed in linear form or in the form of the Cobb-Douglas function. Based on the results of research on respondent farmers who manage cucumber farming in Duriaasi Village, it can be concluded that the income obtained from cucumber farming in Duriaasi Village, Wongeduku District is Rp. 93,271,329,- with an average per Ha of Rp. 15,414,749 ,-. Based on the individual production factors, the influence of the variables SP36 fertilizer (X2) and KCL fertilizer (X4) have a significant effect on income (Y), a significant value of 0.000 < 0.05 is obtained as well as urea fertilizer (X1) and ponska fertilizer (X3). has no significant effect on income (Y), so a significant value of 0.000>0.05 is obtained. The coefficient of determination value symbolized R2 is 0.89